2019
DOI: 10.1001/jamanetworkopen.2018.7660
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Hospital Plumbing

Abstract: In recent years there have been an increasing number of reports of contamination of hospital plumbing with multidrug-resistant gram-negative organisms, with speculation that this contamination poses a significant risk to patients. 1 Hopman and colleagues 2 add to this body of literature with the report of a patient with a carbapenemase-producing Pseudomonas aeruginosa (CP-PA) infection that was shown to be genetically related to a strain of P aeruginosa from the shower in the patient's room. The patient was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The top ranked keyword in cluster 3 is "aerosols", which is often underestimated in disease transmission. Aerosolized transmission of pathogens, such as antibiotic-resistant Pseudomonas aeruginosa and Pseudomonas putida, has been reported in previous studies (Gormley et al, 2017;Snitkin, 2019). Likewise, recent studies confirm aerosolized transmission of Covid-19 through air ducts in bathrooms, toilet facilities, and wastewater discharged from WWTPs (Ding et al, 2021;Gholipour et al, 2021;Hwang and Foster, 2008).…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…The top ranked keyword in cluster 3 is "aerosols", which is often underestimated in disease transmission. Aerosolized transmission of pathogens, such as antibiotic-resistant Pseudomonas aeruginosa and Pseudomonas putida, has been reported in previous studies (Gormley et al, 2017;Snitkin, 2019). Likewise, recent studies confirm aerosolized transmission of Covid-19 through air ducts in bathrooms, toilet facilities, and wastewater discharged from WWTPs (Ding et al, 2021;Gholipour et al, 2021;Hwang and Foster, 2008).…”
Section: Methodssupporting
confidence: 54%
“…Sanger sequencing (SS) is useful for detection of pathogen mutations and has been utilized in the identification of Covid-19 variant in WWTP and antibiotic-resistant pathogens in plumbing systems (Snitkin, 2019;Westhaus et al, 2021). Compared to SS, genome sequencing (GS) is faster, requires less personnel and less space requirements, and has higher throughput and costeffective.…”
Section: Lab Only 4%mentioning
confidence: 99%
See 1 more Smart Citation
“…This propagator pair was able to act as a reservoir of blaIMP-4, likely through occupying an environmental niche as we noted during sampling of ICU sinks. The colonisation of hospital plumbing by CPOs has been well documented 9,[28][29][30][31] , including blaIMP-4harbouring S. marcescens in an Australian setting that was unable to be eradicated 32 . This environmental colonisation enabled not only clonal spread of blaIMP-4 harbouring S. marcescens but also drove diversification through inter-strain transfer of blaIMP-4 IncC plasmids and inter-plasmid transfer of the blaIMP-4 class I integron.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have identified the problem with pathogens in the drains of hospital sinks, and multiple solutions have been proposed. A common infection control policy is to flush sink drains with a disinfectant although biofilm regrows after a while (Snitkin, 2019) and some organisms develop drug resistance (Hota et al, 2009). A German study (Doring et al, 1991) of Pseudomonas-Aeruginosa in contaminated sink drains recommended heating the p-trap to kill the microorganisms.…”
mentioning
confidence: 99%